(untitled) (Research, Society and Development, 2022)
Objectives: to describe and analyze, through bibliographical references, the importance of tools for health auditing. Method: this is an integrative review study. The operationalization was developed from the following stages: identification of the guide question, selection descriptors, database selection, application of inclusion and exclusion criteria, subjects identification of the selected studies and analysis and interpretation of results. Results: 10 articles were identified that met the inclusion criteria for being aligned with the guiding question. The content of the articles was analyzed using Bardin’s content technique and emerged the following categories: nursing notes, health education, quality management, protocols for health technologies and clinical protocols and quality indicators. Final considerations: the importance of management tools is highlighted that nurse auditors can execute the audit processor in organizations, considering the globalized and increasingly competitive environment, as such instruments make it possible to achieve goals, streamline the analysis of results and generate reports.